Optimasi Waktu Setup Mesin Extruder dengan Single Minute Exchange of Dies dan Value Stream Mapping untuk mengurangi Waste Setup Delay - Firdaus Al Amin, Muhammad (SURYA TEKNIKA, 2025)
Amid intense competition in the manufacturing industry, production efficiency is crucial to improving productivity. PT. Manufacturing Sidoarjo, a CPP film producer, faces challenges with long setup times on the extruder machine, reaching up to 296 minutes, comprising 60 minutes for material preparation, 120 minutes for heating, and 60 minutes for trial runs. This issue increases operational costs and reduces competitiveness. The study applies the Single Minute Exchange of Dies (SMED) method to reduce setup time and Value Stream Mapping (VSM) to identify non-value-added activities. As a result, setup time was reduced to 193 minutes, achieving a 34.8% time efficiency, which enhances operational efficiency and production capacity.